Does prison labour rehabilitate, punish, discipline or exploit a traumatised and racialised population in Australian and American prisons? - Andreea Lachsz (Torture)
This article describes the incarcerated population in Australia and the US as being comprised of peo-ple primarily from racialised and marginalised communities, of whom many have histories of trauma. It is argued that their pre-existing trauma is compounded by trauma arising from both deprivation of liberty in and of itself, and their treatment and conditions in prison. The article compares and draws parallels between rehabilitation as understood under the UN Convention against Tortureand Other Cruel, Inhuman or Degrading Treatment or Punishment with rehabilitation as an objective of the criminal legal system, arguing for the need for the criminal legal system to refocus from reducing reoffending to pursuing healing. The article argues that contemporary prison labour in Australia and the US should be analysed in the context of historical slavery and forced labour. It considers the different objectives of prison labour, concluding that it is not feasible to effectively achieve multiple objectives (e.g. rehabilitation versus recouping State costs associated with incarceration). The signifi-cant risk that prison labour as it currently operates can amount to exploitative or degrading treatment is explored in the article, which argues that international legal protections need to be strengthened. The article also recommends that there needs to be improved transparency and research regarding the use and effectiveness of prison labour in these jurisdictions (and more broadly) in achieving rehabili-tation, particularly livelihoods in the community, after release from prison.